(untitled) (Revista de Letras Norte@mentos, 2018)
This study investigated some of the beliefs two teachers of English as an additional language heldtowards approaching culture during their classes. For such, data were collected through individualinterviews with the participants, classroom observation and field notes. Data showed that bothteachers perceived approaching cultural aspects as an important part of their teaching practices,since it provided opportunities to foster significant connections that could assist in the students’learning process. However, both participants pointed out that controversial topics might emergewhen working with cultural aspects. This may lead teachers in general to feel insecure orunprepared to deal with such aspects, ignoring them in their lessons.